2022
DOI: 10.3390/s22218255
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Early Detection of Physical Activity Behaviour Changes from Wearable Accelerometer Data

Abstract: Wearable accelerometers record physical activity with high resolution, potentially capturing the rich details of behaviour changes and habits. Detecting these changes as they emerge is valuable information for any strategy that promotes physical activity and teaches healthy behaviours or habits. Indeed, this offers the opportunity to provide timely feedback and to tailor programmes to each participant’s needs, thus helping to promote the adherence to and the effectiveness of the intervention. This article pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A bout is defined as continuous physical activity at a certain intensity level. 27 The length of a bout is defined as the number of seconds spent during that period. For example, a participant spending 10 seconds in moderate intensity physical activity followed by 4 seconds of vigorous physical activity, then 10 seconds of light activity would generate one bout of moderate-to-vigorous physical activity (MVPA) lasting 14 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A bout is defined as continuous physical activity at a certain intensity level. 27 The length of a bout is defined as the number of seconds spent during that period. For example, a participant spending 10 seconds in moderate intensity physical activity followed by 4 seconds of vigorous physical activity, then 10 seconds of light activity would generate one bout of moderate-to-vigorous physical activity (MVPA) lasting 14 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…25 We used the thresholds of 3, 10, and 30 s for MVPA and 60, 120, and 300 s for sedentary bouts based on a previous study that showed a high dispersion between children’s cumulative sum of physical activity levels. 27 Separating the physical activity bouts by these thresholds allowed us to create meaningful features and generate cohesive clusters. After data normalisation and using the Principal Components Analysis to maximise the variance of our data, we retained three principal components and applied the k-means unsupervised algorithm with k = 5 for the daily movement clusters and k = 4 for hourly movement clusters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations